ANALISIS PENENTUAN SEKTOR UNGGULAN PEREKONOMIAN KOTA SINGKAWANG DENGAN PENDEKATAN SEKTOR PEMBENTUK PRODUK DOMESTIK REGIONAL BRUTO ( PDRB ) - ME, URAY DIAN NOVITA (Jurnal Ekonomi Daerah (JEDA), 2013)
ABSTRAK This research is focused to determine the regional leading sector of Singkawang City. Secondary data such as time series of the Gross Regional Domestic Product (GRDP) of Singkawang City and West Borneo province in the period 2006 2010 are applied. Klassen Typology, Location Quotient (LQ) and Shift Share are tools of analysis. Klassen Typology indicates that the developed sectors are electricity, gas and water supply, construction and trade, hotel and restaurant. Location Quotient analysis indicates mining and quarrying, electricity, gas and water supply, construction, trade, hotel and restaurant, finance, leasing and business service and service are base sector. Shift Share analysis indicates that the competitive sectors are manufacturing industry, electricity, gas and water supply, construction, trade, hotel and restaurant. The results of the analysis based on three analysis tools indicate that the leading sector with the criteria.s developed, base, and competitive is construction sector. Keywords : Leading Sector, Klassen Typology, Location Quotient, and Shift Share.